PENANGANAN BAGI PEJABAT PEMERINTAH YANG TIDAK MELAKSANAKAN PUTUSAN PENGADILAN TATA USAHA NEGARA - Andre Lumban Batu; Tri Hayati (UNES Law Review, 2023)
The study aimed to discover an understanding of the handling of government officials who do not carry out the decisions of the State Administrative Court. In the mechanism for implementing decisions, the State Administrative Court has no implementing agency, and hence, the State Administrative Officers often disobey and do not implement the decisions of the State Administrative Court. Therefore, citizens' constitutional rights to justice decided by the State Administrative Court can be threatened. This study aimed to compare the state administrative justice systems in Indonesia and Thailand. This research uses doctrinal research with a statutory approach. The results of this study are that there is no institution for implementing the decisions of the State Administrative Court in Indonesia. Meanwhile, in Thailand, there is already an implementing agency, and functionally the executive body executes litigants. Therefore, regulation and implementation of State Administrative Officers who do not implement State Administrative Court Decisions is an urgency to increase the effectiveness of implementing State Administrative Court decisions in Indonesia.